Ruminant meat and milk contain δ-valerobetaine, another precursor of trimethylamine N-oxide (TMAO) like γ-butyrobetaine. (15th September 2018) - Servillo, Luigi; D'Onofrio, Nunzia; Giovane, Alfonso; Casale, Rosario; Cautela, Domenico; Castaldo, Domenico; Iannaccone, Francesco; Neglia, Gianluca; Campanile, Giuseppe; Balestrieri, Maria Luisa
Highlights: δ-Valerobetaine is reported for the first time in ruminant meat and milk. δ-Valerobetaine is more abundant in meat and milk of ruminants than non-ruminants. δ-Valerobetaine originates in the rumen from N ε -trimethyllysine. δ-Valerobetaine, producing trimethylamine in the gut, could be a health risk factor. δ-Valerobetaine highlights the importance of N ε -trimethyllysine in vegetables. Abstract: Quaternary ammonium compounds containing N -trimethylamino moiety, such as choline derivatives and carnitine, abundant in meat and dairy products, are metabolic precursors of trimethylamine (TMA). A similar fate is reported for N ε -trimethyllysine and γ-butyrobetaine. With the aim at investigating the metabolic profile of such metabolites in most employed animal dietary sources, HPLC-ESI-MS/MS analyses on ruminant and non-ruminant milk and meat were performed. Results demonstrate, for the first time, the presence of δ-valerobetaine, occurring at levels higher than γ-butyrobetaine in all ruminant samples compared to non-ruminants. Demonstration of δ-valerobetaine metabolic origin, surprisingly, showed that it originates from rumen through the transformation of dietary N ε -trimethyllysine. These results highlight our previous findings showing the ubiquity of free N ε -trimethyllysine in vegetable kingdom. Furthermore, δ-valerobetaine, similarly to γ-butyrobetaine, can be degraded by host gut microbiota producing TMA, precursor of the proatherogenic trimethylamine N-oxide (TMAO), unveiling its possible role in the biosynthetic route of TMAO.